Posttraumatic epilepsy in intensive care unit-treated pediatric traumatic brain injury patients - Era D.Mikkonen; Markus B. Skrifvars; Matti Reinikainen; Stepani Bendel; Ruut Laitio; Sanna Hoppu; Tero Ala-Kokko; Atte Karppinen; Rahul Raj (WILEY, 2022)
Objective Posttraumatic epilepsy (PTE) is a well-described complication of traumatic brain injury (TBI). The majority of the available data regarding PTE stem from the adult population. Our aim was to identify the clinical and radiological risk factors associated with PTE in a pediatric TBI population treated in an intensive care unit (ICU).
Methods We used the Finnish Intensive Care Consortium database to identify pediatric (<18 years) TBI patients treated in four academic university hospital ICUs in Finland between 2003 and 2013. Our primary outcome was the development of PTE, defined as the need for oral antiepileptic medication in patients alive at 6 months. We assessed the risk factors associated with PTE using multivariable logistic regression modeling.
Results Of the 290 patients included in the study, 59 (20%) developed PTE. Median age was 15 years (interquartile range [IQR] 13-17), and 80% had an admission Glasgow Coma Scale (GCS) score <= 12. Major risk factors for developing PTE were age (adjusted odds ratio [OR] 1.08, 95% confidence interval [CI] 1.00-1.16), obliterated suprasellar cisterns (OR 6.53, 95% CI 1.95-21.81), and an admission GCS score of 9-12 in comparison to a GCS score of 13-15 (OR 2.88, 95% CI 1.24-6.69).
Significance We showed that PTE is a common long-term complication after ICU-treated pediatric TBI. Higher age, moderate injury severity, obliterated suprasellar cisterns, seizures during ICU stay, and surgical treatment are associated with an increased risk of PTE. Further studies are needed to identify strategies to decrease the risk of PTE.